Transformation of carbamazepine dihydrate to anhydrous carbamazepine - Noraini, Ghazali (2015)
An investigation of carbamazepine dihydrate transformation to anhydrous carbamazepine was presented. In this works, carbamazepine dihydrate and solvents (ethanol, methanol, propanol, acetonitrile, ethyl acetate and methyl acetate) were used. The crystallization process was conducted using different solvents by applying solid state method using differential scanning calorimetry analysis and solution based method. For solution based method, three conditions of the experiment were implemented i.e. dissolution with heating and cooling without stirring, dissolution with heating and cooling with stirring, dissolution with heating and stirring followed by cooling without stirring. Solid state characterization of the crystals were analysed using Differential Scanning Calorimetry (DSC) and Powder X-Ray Diffraction (PXRD). Analysis data obtained from DSC revealed that the crystals produced from the transformation of carbamazepine dihydrate to anhydrous carbamazepine using solid state and solution based method were not successful. From DSC analysis, the melting point of carbamazepine dihydrate with six solvents for both methods were in the range of 70-160oC. The finding from DSC analysis showed that the melting point of crystals did not fall within the melting point value of the anhydrous form. Referring to the PXRD analysis, the pattern profile of carbamazepine in six solvents with three different conditions does not similar to the literature for the indicative peaks of anhydrous form. It was suggested that the crystals obtained from the dissolution of carbamazepine dihydrate with six solvents using three different conditions were unsuccessful to transform carbamazepine dihydrate to anhydrous carbamazepine. Further study using different techniques and conditions were suggested in order to study the transformation of carbamazepine dihydrate to anhydrous carbamazepine.